Response and Suggestions for: Factors Associated with Burnout Among Physicians: an Evaluation During a Period of COVID-19 Pandemic [Letter] - Almohtadi A; Seyedzenouzi G (Dove Medical Press, 2020)
Ahmad Almohtadi, Golnoush Seyedzenouzi St George’s University of London, Tooting, London SW17 0RE, UKCorrespondence: Golnoush Seyedzenouzi Email m1501591@sgul.ac.uk We read with great interest the article by Dinibutun SR1 evaluating the prevalence and extent of burnout among physicians, factors affecting burnout and the influence of the COVID-19 pandemic on burnout syndrome. Healthcare systems are increasingly becoming stretched for staff and resources, especially during the COVID-19 pandemic, adding to the existing pressure on healthcare workers.2 Therefore, this article comes at a critical time to allow for a better understanding of the factors leading to burnout, allowing for mitigation to improve patient outcomes, work flow and productivity.   View the original paper by Dinibutun